APLIKASI PENCARIAN PARKIR JAKARTA BERBASIS ANDROID MENGGUNAKAN RESTFUL API - Muhammad Adam Dzulqarnain; Muhammad Luthfi Aziz; Muhammad Fauzi Rachman; Aldy Rialdy Atmadja (Masoem University, 2018)
Jakarta is one of the metropolitan cities in Indonesia. The increasing number of vehicles entering Jakarta has resulted in the difficult to find parking area. Moreover, the population density occurred in there also resulted in the difficulty of finding parking area. Each parking area have its own capacity, the driver must directly check the state of the parking area. According to a survey conducted by VIVA, it takes 21 minutes to find parking in Jakarta (Viva, 2017). Based on the background of the problem, it can be conclude, the focus of the research is how to implement RESTFul API on an android application , so it will be ease to find a parking area in Jakarta. The system development method uses Scrum, the implementation results in the form of an android-based application using the RESTFul API.